Environmental Health Risk Analysis of Sulfur Dioxide (SO2) Inhalation Exposure in Ambient Air Among the Tirtonirmolo Community, Bantul. - Musfirah, Musfirah; Ahmad Faizal Rangkuti; Isana Arum Primasari; Ichtiarini Nurullita Santri; Babucarr Jassey; Abril Tafa'ul Lana (Universitas Airlangga, 2024)
Introduction: Sulfur dioxide (SO2) is one of the gases that can pollute the ambient air and cause respiratory irritation. This study aims to determine the characterization of health risk and risk management of sulfur dioxide (SO2) exposure to prevent health impact in the Tirtonirmolo community, Bantul. Methods: This study was a quantitative descriptive research with an Environmental Health Risk Analysis (EHRA) approach. The study subjects were the Tirtonirmolo community in Bantul, with a sample of 110 respondents. The sampling method uses purposive sampling. Results and Discussion: Most respondents are female (74%) with ages over 54 years (52%), and the majority work as housewives (44%). The description of EHRA variables consists of an inhalation rate of 0.83 m3/hour, exposure time of 22 hours/day, exposure frequency of 354 days/year, and exposure duration for real-time projections of 35 years and 30 years for lifetime projections. The SO2 measurement results did not exceed the national quality standard, with the highest concentration being on Madukismo Road, with a concentration of 11.72 Î¼g/m3. The dose-response analysis uses data from the US-EPA, which is 0.026 mg/kg/day. The real-time average intake value is 0.0039 mg/kg/day, and the 30-year lifetime average intake value is 0.0033 mg/kg/day. Conclusion: All respondents from this study had an RQ value<1, both in the RQ for real-time and lifetime. Risk management needs to reduce health risk by using masks when doing outdoor activities and installing Flue Gas Desulfurization (FGD) in factories that emit SO2 emissions.